A two-photon AIE fluorophore as a photosensitizer for highly efficient mitochondria-targeted photodynamic therapy. (26th May 2020) - Kong, Qunshou; Ma, Boxuan; Yu, Tao; Hu, Cheng; Li, Gaocan; Jiang, Qing; Wang, Yunbing
Abstract : Nowadays, photodynamic therapy (PDT) has become an effective method for cancer therapy. Abstract : Nowadays, photodynamic therapy (PDT) has become an effective method for cancer therapy. However, there are still some drawbacks with common photosensitizers including poor photostability, nonspecific targeting, poor tissue penetration depth, low PDT efficiency, etc. Therefore, the development of high-performance photosensitizers is highly desirable. In this study, we design an aggregation-induced emission (AIE) photosensitizer TBBP based on a D–π–A skeleton. This photosensitizer TBBP exhibits strong aggregation-induced emission, large two-photon absorption cross-section, high specificity to mitochondria, deep tissue imaging with a penetration depth up to 150 μm and excellent biocompatibility, showing great potential as a bioprobe in two-photon cell and tissue bioimaging. Furthermore, a higher PDT efficiency than the most commonly used commercial photosensitizer Ce6 has been shown for TBBP owing to the efficient 1 O2 generation, the high 1 O2 quantum yield and the enhanced endocytosis. The two-photon cell and deep tissue bioimaging and highly efficient mitochondria-targeted photodynamic therapy endow this AIE fluorophore TBBP with great potential in clinical applications.